1983
DOI: 10.1071/wr9830499
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fencing to Control Feral Pig Movement

Abstract: Eight fence designs with and without electrification were tested for their ability to stop feral pigs crossing from one paddock to another.Fences of 8:80: 15 hingejoints were pig-proof, whereas fences of 6:70:30 hingejoint or plain wires allowed some pigs to cross. Electrification of the fences significantly reduced the frequency of pig movement through fences to as little as 6.3% of test pigs. The behaviour offeral pigs relative to the fences and their implications are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 3 publications
1
40
0
Order By: Relevance
“…When pigs are nocturnally active, recreational hunting would only be an effective pig control strategy in agricultural fields, as some have suggested (Geisser and Reyer 2004;Hone and Atkinson 1983), if regulations allowed hunting at night. Only 3% of wild pig encounters in this study were recorded during the legal hunting hours.…”
Section: Controlling Pig Access To Farmsmentioning
confidence: 99%
See 2 more Smart Citations
“…When pigs are nocturnally active, recreational hunting would only be an effective pig control strategy in agricultural fields, as some have suggested (Geisser and Reyer 2004;Hone and Atkinson 1983), if regulations allowed hunting at night. Only 3% of wild pig encounters in this study were recorded during the legal hunting hours.…”
Section: Controlling Pig Access To Farmsmentioning
confidence: 99%
“…While field trials have produced fence designs that will contain pigs (Lavelle et al 2011), Hone and Atkinson (1983) found that pigs can breach many types of fences and learn where they are most easily breached. Previous studies found that wild pigs tend to access fields closest to a wildland edge (Geisser and Reyer 2004;Thurfjell et al 2009).…”
Section: Tejon Ranch Conservancymentioning
confidence: 99%
See 1 more Smart Citation
“…Wild boar-proof fences are described and have mainly been used to protect valuable agricultural or ecological environments or to facilitate shooting in Europe and elsewhere (Hone and Atkinson, 1983;Reidy et al, 2008;Bruland et al, 2010;Saito et al, 2011;Honda et al, 2009Honda et al, , 2011Lavelle et al, 2011). This is usually smallscale fencing.…”
Section: Effect Of Feeding or Artificial Physical Barriers In An Asf mentioning
confidence: 99%
“…As long as there is no clear view for instance on the size of the area where animal movement should be restricted, estimations on efficiency, costs and construction time will be inaccurate. Furthermore, wild boar also quickly learn to avoid (electric) fences (Hone and Atkinson, 1983), and double-fencing with an animal-free exclusion zone is usually required to prevent close contact between wild boar and domestic animals. Altogether, a better knowledge on the ASF epidemiologic situation in North East Europe is required to identify the areas where fencing could be used as one element of a control programme and to assess the feasibility of its implementation.…”
Section: Effect Of Feeding or Artificial Physical Barriers In An Asf mentioning
confidence: 99%